Respuesta :
Answer:
f(-3)=g(-3)
Step-by-step explanation:
The graph shows two linear functions that intersect at (-3,-4).
The blue line is f(x).
At the point of intersection:
....eqn1
The blue line is g(x).
At the point of intersection
....eqn2
Equating both equations we get:
The statement that is true regarding the two functions is that:
HOPE THIs HELPS
Answer:
Option 3
g(x) = Negative RootIndex 3 StartRoot x + 4 EndRoot; x greater-than-or-equal-to –4
Step-by-step explanation:
Since the graph starts at x = -4 and towards the right, domain is x 》-4
g(x) = -(x + 4)^⅓
Because,
0 = -(-4 + 4)^⅓
0 = 0